Educação ambiental e recursos hídricos: um olhar sobre Santa Maria – RS - Mastella, Alexandre Dal Forno; Nishijima, Toshio (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2011)
The present study aimed to correlate human actions with environmental problems of the city ofSanta Maria with focus on the theme of water resources. For this, was used the study ofenvironmental perception in two ways: the first consisted to compare the worsening of theenvironmental problems from 10 points of a watercourse located in the urban area of Santa Maria- Sanga da Aldeia; the second wanted to examining the perception of academics of the 8thsemester of Forestry at UFSM regarding environmental problems around the creek Cadena. Held a photographic survey of the 10 points of Sanga da Aldeia. The current state of the watercourse wascompared with the situation in which it found itself in 2008, when it was photographed in thesame places. However the students worked in the classroom issues related to water resourcesmanagement and watched a documentary about Cadena, then answered a questionnaire. Therewas a significant increase in environmental degradation in Sanga da Aldeia, the increase in thenumber of buildings along the banks and the illegal sewage connections, as well as theaccumulation of solid waste (garbage), besides the presence of inappropriate vegetation in thatareas. As for the perception of academics on the Cadena, the majority noted there is a lack ofadequate planning for managing water resources in Santa Maria, and a lake of awarenesspopulation. Then with the aid of environmental perception, it can be stated that the behavior ofthe population, coupled with the lack of commitment by the government, made in a short periodof time, has increased the environmental neglect in relation to resources water and environmentin the city of Santa Maria.